The Bcr-Abl leukemia oncogene activates Jun kinase and requires Jun for transformation. - Raitano, A B (1995)
The leukemogenic tyrosine kinase fusion protein Bcr-Abl activates a Ras-dependent pathway required for transformation. To examine subsequent signal transduction events we measured the effect of Bcr-Abl on two mitogen-activated protein kinase (MAPK) cascades--the extracellular signal-regulated kinase (ERK) pathway and the Jun N-terminal kinase (JNK) pathway. We find that Bcr-Abl primarily activates JNK in fibroblasts and hematopoietic cells. Bcr-Abl enhances JNK function as measured by transcription from Jun responsive promoters and requires Ras, MEK kinase (MAPK/ERK kinase kinase), and JNK to do so. Dominant-negative mutants of c-Jun, which inhibit the endpoint of the JNK pathway, impair Bcr-Abl transforming activity. These findings implicate the JNK pathway in transformation by a human leukemia oncogene.